High-Throughput Screening of Optimal Process Parameters for PVD TiN Coatings With Best Properties Through a Combination of 3-D Quantitative Phase-Field Simulation and Hierarchical Multi-Objective Optimization Strategy - Dai, Rao; Yang, Shenglan; Zhang, Tongdi; Zhong, Jing; Chen, Li; Deng, Chunming; Zhang, Lijun (Frontiers in Materials, 2022)
Physical vapor deposition (PVD) is one of the most important techniques for coating fabrication. With the traditional trial-and-error approach, it is labor-intensive and challenging to determine the optimal process parameters for PVD coatings with best properties. A combination of three-dimensional (3-D) quantitative phase-field simulation and hierarchical multi-objective optimization strategy was therefore developed to perform high-throughput screening of optimal process parameters for PVD coatings, and successfully applied to technically important TiN coating. Large amount of 3-D phase-field simulations of TiN coating growth during PVD process were firstly carried out to acquire the parametric relation among the model parameters, microstructures and various coating properties. Experimental data were then employed to validate the numerical simulation result and reveal the correlation between the model parameters and process parameters. After that, a hierarchical multi-objective method was proposed for design of multiple coating properties based on the quantitative phase-field simulations and key experimental data. Marginal utility was subsequently examined based on the identification of the pareto fronts in terms of various combination of objectives. The windows for best TiN coating properties were therefore filtered with respect to the model/process parameters in a hierarchical manner. Finally, the consistent optimal design result was found against the experimental results.